Roles of Local and Newcomer Entrepreneurs in Rural Development: A Comparative Meta-analytic Study - Akgün, Aliye A.; Baycan-Levent, Tuzin; Nijkamp, Peter; Poot, Jacques (Informa UK Limited, 2011)
Roles of local and newcomer entrepreneurs in rural development: a comparative meta-analytic study, Regional Studies. Early studies of rural development suggested that newcomer rural entrepreneurs are important agents of change and responsible for new spatial development, but more recent research has concluded that there is no difference between newcomer and local rural entrepreneurs in this respect. Much of this literature is based on qualitative ethnographic case studies. Systematic pooling and scrutinizing of the main attributes and findings of such studies enhances their comparability and permits some generalization. Newcomer and local rural entrepreneurship is therefore investigated by means of a meta-analysis of twenty-two applied studies. The statistical results show that newcomer entrepreneurs are relatively older, better educated, and develop more non-agricultural business. They appear to be predominantly attracted by a rural lifestyle. In many cases, newcomer entrepreneurs are not directly the instigators of economic development, but their contribution to physical capital formation is greater than that of the locals. © 2011 Regional Studies Association.
Keywords: meta-analysis; SDG 8 - Decent Work and Economic Growth; entrepreneurship; in-migration; rural development